ASME/STLE 2007 International Joint Tribology Conference, Parts a and B 2007
DOI: 10.1115/ijtc2007-44160
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanofluids in Minimum Quantity Lubrication Grinding

Abstract: This research project investigated the wheel wear and tribological characteristics in wet, dry and minimum quantity lubrication (MQL) grinding of cast iron. Water-based Al2O3 and diamond nanofluids were applied in MQL grinding process and the results were compared with those of pure water. During the MQL grinding using nanofluids, a dense and hard slurry layer was formed on the wheel surface and could benefit the grinding performance. Experimental results showed that G-ratio, volume of wear of the grinding whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 3 publications
0
51
0
4
Order By: Relevance
“…Shen [30] experimented and concluded that the application of nanofluid in MQL grinding was evaluated for the first time. It is concluded that nanofluid are not able to provide superior cooling capacity in MQL grinding process.…”
Section: Novel Machining Techniquesmentioning
confidence: 99%
“…Shen [30] experimented and concluded that the application of nanofluid in MQL grinding was evaluated for the first time. It is concluded that nanofluid are not able to provide superior cooling capacity in MQL grinding process.…”
Section: Novel Machining Techniquesmentioning
confidence: 99%
“…They verified the benefits of nanofluids in terms of reducing grinding forces, improving surface roughness, and preventing burning of the workpiece. In contrast to dry grinding, MQL grinding could substantially lower the grinding temperature [1].…”
Section: Introductionmentioning
confidence: 99%
“…Grinding is a precision machining process which is widely used in the manufacture of components requiring fine tolerances and smooth finishes [1]. Therefore, the negative effect of high temperature on these parameters should be prevented [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the application of nanoparticles as a water-based cooling / lubricating medium is very rare [56]. The application of water-based Al2O3 and diamond nanofluids in MQL grinding shows promising improvements in surface roughness, a reduction in the grinding force, and an improved G-ratio with high concentrations of nanofluids as compared to pure water application [57,58]. Research was carried out to investigate the wheel wear and the tribological characteristics in wet, dry and MQL grinding of cast iron.…”
Section: Introductionmentioning
confidence: 99%